2017
DOI: 10.1038/cddis.2017.337
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles harness autophagy to induce cell death in lung epithelial cells

Abstract: Although zinc oxide nanoparticles (ZnONPs) are widely used, they have raised concerns of toxicity in humans. Previous studies have indicated that reactive oxygen species (ROS) and autophagy are involved in the cytotoxicity of ZnONPs, but the regulatory mechanisms between autophagy and ROS remain to be elucidated. Herein, we comprehensively investigated the regulatory mechanism of autophagy and the link between autophagy and ROS in ZnONPs-treated lung epithelial cells. We demonstrated that ZnONPs could induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 69 publications
7
93
0
Order By: Relevance
“…To monitor the autophagic flux in the MLO-Y4 cells, a western blotting assay of endogenous LC3 and p62 proteins was performed as described previously [21] . The cells were collected and then washed with cold PBS and lysed with cold RIPA lysis solution (Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…To monitor the autophagic flux in the MLO-Y4 cells, a western blotting assay of endogenous LC3 and p62 proteins was performed as described previously [21] . The cells were collected and then washed with cold PBS and lysed with cold RIPA lysis solution (Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that ROS and autophagy are involved in the cytotoxicity of ZnO NPs, but the regulatory mechanisms between autophagy and ROS remain to be elucidated. Zhang et al investigated the regulatory mechanism of autophagy and the link between autophagy and ROS in ZnO NPs-treated lung epithelial cells [ 65 ]. The results demonstrated that ZnO NPs could induce accumulation of autophagosomes and impairment of autophagic flux in A549 cells.…”
Section: Biomedical Applications Of Zno Nanoparticlesmentioning
confidence: 99%
“…ZnO NPs are initially recognized by the phagocytes, which further ingest them into the phagosomes, which are then acidified by phagosomes/lysosomes fusion (Cho et al 2011). The resultant dissolution of the ZnO NPs to its ions in the acidic micro-environment inside phagosomes/lysosomes causes lysosomal destabilization and subsequent cell death, which is regarded as the most accepted pathway for ZnO NPs induced toxicity (Pokhrel et al 2009, Cho et al 2011, Zhang et al 2017. ZnO NPs interaction with immune system due to their accumulation in spleen and lymph nodes has been shown in a mice in vivo model (Senapati et al 2017), where ZnO NPs have also been found to induce the release of inflammatory cytokines and causing an imbalance of Th-1/Th-2 cells (Senapati et al 2017).…”
Section: Introductionmentioning
confidence: 99%